(untitled) (Research, Society and Development, 2022)
Variations in carbohydrate metabolism are evident during pregnancy to meet the needs of the fetus. However, when pregnant women present exacerbated physiological alterations of this mechanism associated with maternal predisposition, Gestational Diabetes Mellitus (GDM) is characterized. Pregnant women who have risk factors such as insulin resistance and overweight/obesity are more likely to develop the disease, favoring adverse outcomes for the fetus. Thus, the present study aims to find evidence in the literature of the relationship between overweight/obesity and the development of GDM, given the epidemiology of the disease and its higher prevalence as one of the main complications of the gestational period. The article consists of an integrative literature review, with a publication interval between 2020 and 2022. The following databases were used: Virtual Health Library (VHL); National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (SCIELO), EbscoHost. The results demonstrated a positive relationship between overweight/obesity and GDM, demonstrating that the complications of this relationship affect maternal and fetal health, and may progress to unfavorable outcomes in the infant and adult life of the conceptus. Therefore, the conclusion of this article is in agreement with recent findings in the literature, which show that obesity, when present in pregnant women, is directly related to several disorders both in the mother, such as the development of GDM, and in the fetus, increasing intrauterine and neonatal morbidity and mortality.